2012
DOI: 10.1016/j.neuroimage.2012.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Functional activation of the infant cortex during object processing

Abstract: A great deal is known about the functional organization of the neural structures that mediate visual object processing in the adult observer. These findings have contributed significantly to our conceptual models of object recognition and identification and provided unique insight into the nature of object representations extracted from visual input. In contrast, little is known about the neural basis of object processing in the infant. The current research used near-infrared spectroscopy (NIRS) as a neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 28 publications
3
65
0
1
Order By: Relevance
“…On the basis of these findings, one might expect younger infants, whose visual acuity is less well developed and hence depend more on motion-carried information to perceive object shape, to show greater activation in dorsal areas than older infants. Consistent with this hypothesis, Wilcox et al (2012) found that infants 3 to 5 months, but not infants aged 11 to 12 months, evidence activation in posterior parietal cortex during the different-shape event. Recall that from the early months of life infants individuate on the basis of shape (Wilcox, 1999) and both 3- to 5-month-olds and 11- to 12-month-olds show activation in anterior temporal cortex to the shape difference test event (Wilcox et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…On the basis of these findings, one might expect younger infants, whose visual acuity is less well developed and hence depend more on motion-carried information to perceive object shape, to show greater activation in dorsal areas than older infants. Consistent with this hypothesis, Wilcox et al (2012) found that infants 3 to 5 months, but not infants aged 11 to 12 months, evidence activation in posterior parietal cortex during the different-shape event. Recall that from the early months of life infants individuate on the basis of shape (Wilcox, 1999) and both 3- to 5-month-olds and 11- to 12-month-olds show activation in anterior temporal cortex to the shape difference test event (Wilcox et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
“…Consistent with this hypothesis, Wilcox et al (2012) found that infants 3 to 5 months, but not infants aged 11 to 12 months, evidence activation in posterior parietal cortex during the different-shape event. Recall that from the early months of life infants individuate on the basis of shape (Wilcox, 1999) and both 3- to 5-month-olds and 11- to 12-month-olds show activation in anterior temporal cortex to the shape difference test event (Wilcox et al, 2012). Yet, only the 3- to 5-month-olds show activation in posterior parietal cortex.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…For example, task-based fMRI and FNIRS studies using passive stimuli have revealed adult-like positive blood-oxygen-level-dependent (BOLD) signals in response to sensorimotor 74, 75 , visual 76 , and auditory stimuli 77, 78 in human newborns and infants. FNIRS studies have documented the emergence and gradual improvement of various other functional responses during spatiotemporal processing 79 , object recognition 80 , learning 81 and social processing 82 , among other processes, during the first year of life. Nevertheless, non-invasive brain imaging of awake infants remains challenging owing to their motion and their inability to perform certain tasks, which limit such studies to a restricted set of brain functions.…”
Section: Networkmentioning
confidence: 99%